Performance Planning of Civil Servants in Local Government: A Study at the Regional Personnel and Human Resource Development Agency (BKPSDM) of Bogor City - Perdanaputra, Decky; Hutauruk, Rosina Paulina; Utami, Annisa Aulia (Universitas Sang Bumi Ruwa Jurai, 2021)
This research investigates the performance planning process of civil servants (ASN) at the Regional Personnel and Human Resource Development Agency (BKPSDM) of Bogor City. Using a qualitative case study approach, the study examines the extent to which performance plans are aligned with institutional objectives, measurable, and supportive of individual accountability. Findings reveal that while performance planning instruments such as SKP (Employee Performance Targets) are formally implemented, challenges persist in cascading organizational goals, aligning individual targets, and integrating feedback into performance reviews. The study offers insights into improving planning quality as a foundation for bureaucratic reform and performance-based goverance.